MENTAL HEALTH STATUS AND DRUG USE PATTERN AMONG UNDERGRADUATES IN A NIGERIAN UNIVERSITY - Olutunde, Olatunji Samuel (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The study examined the mental health status of the undergraduates in relation to their pattern of drug use. 240 students including 138 males and 102 females drawn from Ekiti State University participated in the study. General Health Questionnaire and Drug use Scale were employed to collect data. One Way ANOVA and independent t-test were used to test the three hypotheses stated. Result shows that alcohol consumption has a significant effect on somatic symptoms, anxiety and depression, but not on social dysfunction. Results also show how undergraduates vary in their mental health status relating to somatic symptoms, anxiety, depression and social dysfunction. Findings from hypothesis three showed a significant sex difference in drug and alcohol use but not in their mental health.